The Potency of Ageratum conyzoides Leaves Exract to Reduce Mikroorganism in Broiler Intestine - Abdul Hamid; Sulasmi Sulasmi; Faisal Jamin (Jurnal Medika Veterinaria, 2014)
This study was aimed to determine the effect of bandotan (Ageratum conyzoides) leaf extract on the amount of bacteria in broiler intestine. This research consists of 3 treatment groups with 5 replicates. Chickens used were 25 days. Group P0 was control group without administration of bandotan leaf extract, treatment 1 (P1) was given 3ml of bandotan leaf extract, and treatment 2 (P2) was given 4ml of bandotan leaf extract. The extract was given once daily for 5 consecutive days. The result showed that the average amount of microbe on P0, P1, and P2 were 2.50x105, 1.75x105, and 1.34x105.The results of analysis of variance showed that bandotan leaf extract significantly (P0.5) decrease the amount of bacteria in broiler intestines. Based on these results it can be concluded that the effect of bandotan leaf extract inhibit the growth of bacteria in broiler intestine.Key words: broiler, bandotan leaf extract, caecum